2016
DOI: 10.1021/acsami.6b03942
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Palladium Nanoparticles on Porous Aromatic Frameworks as a Sensing Platform to Detect Vanillin

Abstract: Here, we report the fabrication of palladium nanoparticles on porous aromatic frameworks (Pd/PAF-6) using a facile chemical approach, which was characterized by various spectro- and electrochemical techniques. The differential pulse voltammetry (DPV) response of Pd/PAF-6 toward the vanillin (VA) sensor shows a linear relationship over concentrations (10-820 pM) and a low detection limit (2 pM). Pd/PAF-6 also exhibited good anti-interference performance toward 2-fold excess of ascorbic acid, nitrophenol, glutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Therefore, it can be concluded that the oxidation process of vanillin at FePc MOF/GCE involves two protons and two electrons, which is consistent with previously reported results. [50][51][52] The proposed mechanism for vanillin oxidation is shown in Scheme 2.…”
Section: Effect Of Scan Ratementioning
confidence: 99%
“…Therefore, it can be concluded that the oxidation process of vanillin at FePc MOF/GCE involves two protons and two electrons, which is consistent with previously reported results. [50][51][52] The proposed mechanism for vanillin oxidation is shown in Scheme 2.…”
Section: Effect Of Scan Ratementioning
confidence: 99%
“…The analytical parameters were given comparatively between the proposed method and some previous studies in Table . The LOD value of the ATT modified Au electrode is lower than those previously reported in the literature . In general, the synthesis of coating substances and its modification of the electrode surfaces are time‐consuming and complicated, whereas the preparation of the ATT‐Au modified electrode is quick and simple.…”
Section: Resultsmentioning
confidence: 70%
“…Electrochemical sensors are gaining great importance because of their fast response, high sensitivity, cheap instrumentation, online detection ability, etc. (Minematsu et al., 2013; Silva et al., 2015; Veeramani et al., 2015; Vilian et al., 2016; Wang et al., 2015; Wu et al., 2016; Xinying, 2014; Zheng et al., 2010). Recently, different electrochemical sensors were reported for determination of vanillin (Ali et al., 2017; Alpar et al., 2018; Cheraghi et al., 2017; Deng et al., 2015; Jiang et al., 2014; Raril & Manjunatha, 2020; Shang et al., 2014; Shen et al., 2014; Tabanlıgil Calam, 2020; Tian et al., 2020; Yardim et al., 2013).…”
Section: Introductionmentioning
confidence: 99%